2014
DOI: 10.1186/preaccept-1516771013137283
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: shedding light on infertility? - a review of the recent literature

Abstract: In recent years, the negative impact of oxidative stress on fertility has become widely recognised. Several studies have demonstrated its negative effect on the number and quality of retrieved oocytes and embryos following in-vitro fertilisation (IVF). Melatonin, a pineal hormone that regulates circadian rhythms, has also been shown to exhibit unique oxygen scavenging abilities. Some studies have suggested a role for melatonin in gamete biology. Clinical studies also suggest that melatonin supplementation in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 110 publications
(125 reference statements)
0
26
0
Order By: Relevance
“…In human clinical studies, the use of 3 mg melatonin has been demonstrated to improve the oocyte maturation, the fertilization rate, the quality of embryos and the pregnancy outcomes without any obvious physiologic side effects . In our study, the dose of 30 mg/kg body weight of melatonin used in mice is equal to 2.5 mg for human use according to the dose conversion between mouse and human .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In human clinical studies, the use of 3 mg melatonin has been demonstrated to improve the oocyte maturation, the fertilization rate, the quality of embryos and the pregnancy outcomes without any obvious physiologic side effects . In our study, the dose of 30 mg/kg body weight of melatonin used in mice is equal to 2.5 mg for human use according to the dose conversion between mouse and human .…”
Section: Discussionmentioning
confidence: 90%
“…In human clinical studies, the use of 3 mg melatonin has been demonstrated to improve the oocyte maturation, the fertilization rate, the quality of embryos and the pregnancy outcomes without any obvious physiologic side effects. 61 In our study, the dose of 30 mg/kg body weight of melatonin used in mice is equal to 2.5 mg for human use according to the dose conversion between mouse and human. 62 Therefore, our findings provide an implication that melatonin has a potential role in preventing the deterioration of human oocytes exposed to BPA when supplied concurrently, but whether it can reverse the adverse effects of BPA that have already accumulated in oocytes needs the future investigations.…”
Section: Discussionmentioning
confidence: 93%
“…FF rich in antioxidants is absent in oocyte medium cultures including melatonin, which protects oocyte from oxidative stress. Furthermore the ROS level is higher during IVF due to a high oxygen concentration level in incubators and handing throughout the IVF process [ 35 ]. With the increase in “oxidative stress” during IVF, melatonin, with its scavenger properties, finds its proper use.…”
Section: Rationale For the Use Of Melatoninmentioning
confidence: 99%
“…22 It must be considered that excessively high levels of melatonin could reverse these beneficial effects and result in toxicity. 13 Myo-inositol is an isoform of inositol that belongs to the vitamin B complex and is one of the precursors of the synthesis of phosphatidylinositol phosphates, biomolecules that belong to the translation signaling system involving the regulation of several cell processes, such as morphogenesis and cell cytogenesis, the formation of cell membrane, lipid synthesis, and cell growth. 23 Myo-inositol, in fact, is related to oocyte maturation and embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…7 This stress is associated with poor oocyte quality. 7 In recent years, the importance of oxidative stress in ART has become increasingly relevant, particularly for in vitro fertilization (IVF) techniques 12,13 and intracytoplasmic sperm injection (ICSI). 14 One way to reduce the effects of oxidative stress is using antioxidants.…”
Section: Introductionmentioning
confidence: 99%